2002
DOI: 10.1021/la0257384
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Stilbene-Containing Gemini Photosurfactant:  Light-Triggered Changes in Surface Tension and Aggregation

Abstract: A new photosurfactant has been synthesized, and its photoreactions in water, interfacial properties, and changes in aggregation have been characterized. The compound is a stilbene-containing gemini photosurfactant (SGP), which is of interest because the headgroup spacer is a stilbene chromophore, and it may be prepared initially in the trans (E-SGP) form. Molecular simulations show that UV-induced reactions cause significant changes in molecular conformation and especially the relative orientation of hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 44 publications
7
116
0
1
Order By: Relevance
“…However, by using visible and to a lesser degree long wave UV light, it is possible to fabricate materials and dynamically change properties of biomaterials with already attached or embedded living cell cultures [27,28]. Photoisomerizable groups, including the azobenzene group [29], stilbenes [30], and spiropyrans [31,32] have been used to induce disassembly or dissolution of biomaterials. The most commonly used approach to control this material involves photolysis of covalent cross-links, such as 2-nitrobenzyl derivatives [27,28,[33][34][35].…”
Section: Open Accessmentioning
confidence: 99%
“…However, by using visible and to a lesser degree long wave UV light, it is possible to fabricate materials and dynamically change properties of biomaterials with already attached or embedded living cell cultures [27,28]. Photoisomerizable groups, including the azobenzene group [29], stilbenes [30], and spiropyrans [31,32] have been used to induce disassembly or dissolution of biomaterials. The most commonly used approach to control this material involves photolysis of covalent cross-links, such as 2-nitrobenzyl derivatives [27,28,[33][34][35].…”
Section: Open Accessmentioning
confidence: 99%
“…Some light-active and redox-active surfactants have been successfully used to show the reversible changes in aggregation morphology, viscosity, microemulsion separation, and solubilization [20,21]. Besides, research on active control of the interfacial tension has also been reported for designed surfactants using triggers including ultraviolet irradiation [22,23], electrochemical oxidation [24,25] and chemodegradation [26,27]. In previous investigations, amphiphiles containing disulfide bonds have attracted a great deal of attention [28][29][30][31][32][33] mainly because of their ability to be reduced chemically, electrochemically, photochemically, and enzymatically [34].…”
Section: Introductionmentioning
confidence: 99%
“…While after UV irradiation, the effective domain size detected by DLS increases from 73 to 137 nm, this final state is still smaller than the original size (197 nm). On the basis of photochemical studies [15][16][17][18][19], the post-irradiation structures consist of mixed block co-polymer/hexylbenzene/hexylphenol/sodium hydrogen sulfate aggregates, where hexylbenzene is the dominant photoproduct. Thus, after irradiation the average domain size of L α -B might be expected to differ from the original L α -A phase.…”
Section: Saxs and Sansmentioning
confidence: 99%
“…This electrostatic effect can be eliminated by changing the ionic strength of the solution, through adding inert electrolyte. Recently, light has been used as a method to control vesicle stability [14][15][16][17][18]; this is an attractive approach because it is not necessary to change thermodynamic variables or the system chemical composition. Extensive studies involving an anionic photolyzable surfactant, sodium 4-hexylphenylazosulfonate (C 6 PAS), showed that UV light can provoke the breakdown of microemulsions formulated from mixtures with inert Aerosol-OT [19,20].…”
Section: Introductionmentioning
confidence: 99%